Operational Strategy of the un RDB Task Force in Supporting the Success of the Monusco Mission in the Democratic Republic of Congo (Case Study: Monusco RDB Task Force, 2018) - Muhammad Fahri Prawira; Thomas; Tasdik (Journal of Education Religion Humanities and Multidiciplinary, 2026)
Prolonged armed conflict in the eastern region of the Democratic Republic of the Congo has resulted in escalating violence, humanitarian crises, and security instability, despite the United Nations peacekeeping mission through MONUSCO having operated for more than two decades. As a combat unit within the framework of robust peacekeeping, the Rapid Deployment Battalion (RDB) Task Force is expected to suppress the activities of armed groups while protecting civilians. However, various reports indicate that violence against civilians continues to occur, suggesting that operational effectiveness has not yet been fully achieved. This study aims to analyze the factors influencing the operational performance of the RDB Task Force and to examine the operational strategies implemented to support the success of the MONUSCO mission. The study employed a qualitative research method with a case study approach. Data were collected through interviews, observations, and document analysis. The analysis was based on Carl von Clausewitz's theory of military strategy, the United Nations Peacekeeping Operations Doctrine (2008), and Arthur F. Lykke Jr.'s Ends, Ways, Means strategic framework. The findings indicate that the RDB Task Force's operations are influenced by internal factors, including personnel competence, command structure, discipline, and logistical support, as well as external factors such as multinational cooperation, support from local authorities, the dynamics of armed groups, and the geographical conditions of the operational area. The operational strategies implemented include the integration of offensive operations and civilian protection, multinational coordination, personnel capacity building, optimization of logistical support, and the utilization of modern technology and intelligence. The study concludes that the success of the MONUSCO mission depends on the RDB Task Force's ability to optimize its internal factors and adaptively manage external factors through an integrated operational strategy to enhance operational effectiveness and civilian protection.